Biotransformation potential of 6:2 fluorotelomer sulfonate (6:2 FTSA) in aerobic and anaerobic sediment. (July 2016) - Zhang, Shu; Lu, Xiaoxia; Wang, Ning; Buck, Robert C.
Abstract: Aqueous film-forming foam (AFFF) products are used in industrial and military firefighting around the globe. These products contain fluoroalkylthioamido sulfonates, fluoroalkylthiobetaine, and other related substances as the major ingredients, which can be biotransformed in the environment to form 6:2 fluorotelomer sulfonate (6:2 FTSA, F(CF2 )6 CH2 CH2 SO3 ˉ) as one of the major initial biotransformation products. Limited information is available on 6:2 FTSA aerobic biotransformation in activated sludge and pure microbial culture. This is the first study to report 6:2 FTSA biotransformation in aerobic and anaerobic sediment. 6:2 FTSA was rapidly biotransformed in aerobic river sediment with a half-life less than 5 d. Major stable transformation products observed after 90 d included 5:3 Acid [F(CF2 )5 CH2 CH2 COOH), 16 mol%), PFPeA [F(CF2 )4 COOH, 21 mol%] and PFHxA (F(CF2 )5 COOH, 20 mol%). 6:2 fluorotelomer alcohol [6:2 FTOH, F(CF2 )6 CH2 CH2 OH] was readily biotransfomed whereas 6:2 FTSA biotransformation did not occur in anaerobic sediment over 100 d, indicating that the enzymatic desulfonation step limited 6:2 FTSA biotransformation in anaerobic sediment. These results suggest that 6:2 FTSA related products, after release to the aerobic environment, is likely to biodegrade forming 5:3 Acid, PFPeA and PFHxA. This study also indicates that 6:2 FTSA formed from its aforementioned precursors may be persistent in the anaerobic environment after their potential release. This work provides insight to understanding the fate and environmental loading of AFFF-related products and their major transformation products in the environment. Highlights: 6:2 FTSA aerobic and anaerobic biotransformation in sediments was examined for the first time. 6:2 FTSA aerobic biotransformation in sediment yielded PFPeA, PFHxA, and 5:3 Acid. 6:2 FTSA was not biotransformed in anaerobic sediment whereas 6:2 FTOH was readily transformed. Microbial desulfonation of 6:2 FTSA was the rate-limiting step.